Pengaruh Mobilitas Penduduk Terhadap Penyebaran HIV dengan Menerapkan Model Seir - Sahrudin Sahrudin; Dwi Andini; Sandrina Malakiano Ritonga; Intan Janurianty; Ade Widya (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2025)
Human Immunodeficiency Virus (HIV) is a virus that causes Acquired Immunodeficiency Syndrome (AIDS). This virus attacks the immune system by destroying one of its important elements, namely white blood cells known as T lymphocytes or lymphocyte cells. This study aims to analyze the influence of population mobility on the spread of HIV in North Sumatra Province using the SEIR (Susceptible, Exposed, Infected, Recovered) model. The data used includes the population and new HIV cases in 2023 in 33 districts/cities in this region. The SEIR model was modified to take into account the level of population mobility to calculate the disease transmission rate. The results of the analysis show that areas with high levels of mobility, such as Medan and Deli Serdang, have a significant number of new HIV cases, 1,200 and 144 cases respectively. In contrast, areas with small populations and low mobility, such as Pakpak Bharat and North Nias, recorded low or no HIV cases. This research shows a correlation between population mobility and the spread of HIV, so prevention strategies are needed that focus on areas with high levels of mobility.